HBR's 10 must reads 2017 :the definitive management ideas of the year from Harvard business review (HBR's 10 must reads/)
The Harvard Business Review to help you get up to speed fast on the relevant trends driving business today. Revisit these topics now to make sure you re incorporating the smartest, most up-to-date thinking in your organization, or keep this book as a reference so you can access these important pieces when you need them most. The collection includes articles on leadership, strategy, and innovation, as well as articles that will help you manage yourself and others.